Effectiveness of a Positive Youth Development Program for Secondary 1 Students in Macau: A Pilot Study - Andrew L. Luk; Annah M. L. Au; K. M. Leong; Michelle M. X. Zhu; G. B. Lau; Tammy C. P. Wong; Nancy W. I. Lei (The Scientific World Journal)
With the rapid change to society after the opening of the gaming licensure by the government and the potential attraction to youth caused by the casinos, a well-tested and comprehensive adolescent development program previously established in Hong Kong was adopted and modified to be used in Macau. It is expected to help our adolescents achieve positive growth and be better prepared for future challenges. The aim of this study is to examine the effectiveness of the modified positive youth development program for Secondary 1 Students in Macau. Specifically, two research questions will be asked: (1) How does the positive youth development program affect positive growth for youth in Macau?; and (2) Is youth growth related to different factors such as gender, age, family financial condition, and parents' marital status? A mixed research method with a quantitative approach using a pre- and post-test pre-experimental design, and a qualitative approach using a focus group for the participants is carried out. The study sample included 232 Secondary 1 Students in two schools. The objective outcome evaluation showed that, overall, 123 (53%) of the participants had significant improvement on the total scores of the Chinese Positive Youth Development Scale (CPYDS) and the two composite scores. However, there were some increases in the behavioral intention of alcohol drinking and participation in gambling activities. The “happiness of the family life” was found to have significant differences in the score of the CPYDS, which was shown to be the factor related to youth growth. The focus group interviews revealed that both positive and negative feedback was obtained from the discussion; however, the majority of the participants perceived benefits to themselves from the program. With reference to the principle of triangulation, the present study suggests that, based on both quantitative and qualitative evaluation findings, it should be concluded that there is positive evidence supporting the effectiveness of the Tier 1 Program of the Hong Kong Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes), which was adopted and modified for Macau. In addition, special attention should be paid to the behavioral intention of alcohol drinking and participation in gambling activities in the local context.